Healthcare avoidance: a qualitative study of dental care avoidance in Germany in terms of emergent behaviours and characteristics - Isabell Gragoll; Lukas Schumann; Monique Neubauer; Christina Westphal; Hermann Lang (BMC, 2021)
Abstract Background The treatment of acute pain is part of everyday dental practice. Often, these symptoms result from years of patients' inadequate or missing dental routines and lead to a reduction in the quality of life or health of the patients and to high costs for the health care system. Despite the enormous advantages of modern dentistry, many patients avoid going to the dentist. Therefore, the study aimed to determine the reasons and behaviours that cause patients to avoid visits to the dentist. Methods We conducted semi-structured interviews with patients who had an above-average DMFT index and had been going to the dentist only irregularly for years. The sample participants were recruited from the northern German region of Mecklenburg-Western Pomerania. 20 individual interviews were recorded, transcribed verbatim and coded. We used a qualitative framework approach to code the transcripts in order to establish a consensus among the researchers. Ultimately, through discussions and reviews of the attributes and meaning of the topics, a typology could be established. Results A typology of patients who avoid the dentist was developed. Four independent characteristic patterns of dentist avoidance could be developed: avoiding the dentist due to "distance" (type A; includes subtype A1 "avoiding the dentist due to negligence" and subtype A2 "dental avoidance due to neutralization"), "disappointment" (type B), "shame" (type C), and "fear" (type D). Using the typology as a generalised tool to determine the minimum and maximum contrasts, it was possible to capture the diversity and multidimensionality of the reasons and behaviours for avoidance. All patients had negative dental experiences, which had led to different avoidance patterns and strategies. Conclusions The identified avoidance characteristics represent a spectrum of patients from Northern Germany who avoid going to the dentist. This is the first comprehensive study in Germany representing avoidance behaviour of dentist patients in the form of a typology. The results suggest that dentistry also needs qualitative research to better understand patient characteristics and provide direct access to patients who avoid regular dental visits. Thus, the results make a potentially fundamental contribution to the improvement of dental care and enrich its understanding.